THE SIGNALS OF DIVIDEND - Budiarso, Novi Swandari (ACCOUNTABILITY, 2018)
Dividend decisions is a type of policy that earnings should be distributed to shareholders and sometimes contrast with the interest by insiders whether to retain or reinvest. The objective of this study is to examine the determinants of dividend policy on 230 listed firms in period of 2010 to 2011 and conducts logistic regression for hypothesis testing. This study finds that profitability, firm size, and institutional ownership are significant to dividend policy while managerial ownership is insignificant. This findings indicate that most of listed firms of the sample of this study determine the dividend policy based on profits. This study also finds that more larger the firms or institutional ownership then they tend to increase the dividends. Limited to sample, this study proves that agency theory is not applicable for dividend policy in Indonesia as the managerial ownership have no relationship with the dividend policy.